Letter from the Climax Molybdenum Company to Max Bredig - Loeb, Carl M. (1943)
Letter requesting financial support of the Boy Scouts of America from Max Albert Bredig (1902-1977).
Keywords: Boy Scouts of America; Bredig, Max Albert, 1902-1977; Climax Molybdenum Company